(The Role of Financial Inclusion in Providing Protection to Beneficiaries of Financial Services in the Palestinian Banking Sector (2013/2017 - Shaheen, Yasser Ahmed (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed at examining some of the indicators of financial inclusion in the Palestinian banking sector through published secondary data on the Palestinian banking sector during the period (2013- 2017), as well as to measure the degree of protection for beneficiaries of financial services in the Palestinian banking sector.The researcher used the descriptive analytical method to suit the purposes of the study. The secondary data published and prepared by the researcher were used to examine the state of financial coverage in the banking sector. A questionnaire has been designed for the purpose of collecting preliminary data regarding the level of protection provided by the banking sector to users of financial banking services through 8 areas of protection developed after reference to literature and previous studies.The study population consisted of all the beneficiaries of banking financial services in the West Bank. In view of the large size of the study society, a soft sample of (100) conditional on the characteristics of the respondents was used in terms of (banking culture, years of experience in dealing with banks, Sectoral& banking diversification).The researcher reached the following results:- The Palestinian banking sector promotes the reality of financial inclusion, which contributes significantly to enhancing financial stability. Where banks are strengthening protection for users of banking services, although the level of protection was average (2.78) overall score through the eight areas covered by the study.- The regulatory and supervisory role of the Palestinian Monetary Authority in this important sector was medium. Consumer protection bodies are required to have an active and proactive role to organize the required protection.The researcher recommended the importance of financial education to improve the financial personality of individuals and institutions, help them understand their rights and duties in dealing with the services discharged, the importance of the consumer protection associations roles in enhancing banking protection.
Keywords: financial inclusion; consumer protection for financial services; the Palestinian banking sector